Impact of Packet Size in Adaptive Cognitive Radio Sensor Network. (9th December 2018) - Al-Medhwahi, Mohammed; Hashim, Fazirulhisyam; Ali, Borhanuddin Mohd; Sali, A.
Abstract : A cognitive radio sensor network (CRSN) is a solution that enables sensor nodes to opportunistically access licensed radio channels. Data transmitted over a network are divided into packets. In machine-to-machine communication, which is a heterogeneous nature of wireless networks, small-size packets are the common form of traffic. Due to the nature of CRSNs, small data packets will not allow a balance between optimal performance of the network and fulfilling the secondary network obligations towards the primary network in terms of interference. Either interference or channel's underutilization would result from employing data packets of inadequate size. In this paper, the appropriate packet size for adaptive CRSN is investigated by examining the performances of small, medium, and large packet size. In contrast to the trends of exploiting small packets of sizes up to 128 bytes, this study demonstrates that medium-size packets are more appropriate to yield the best performance in CRSNs. Simulation results show that packets of size 375 bytes outperform smaller and larger packets in many CRSN protocols. The induced delay that is partially caused by interference is decreased at the same time the channels are efficiently utilized.